Optimasi Pemilihan Tempat Wisata Karawang Menggunakan FuzzyTOPSIS - Handayani, Popon; Aziz, Faruq (JATISI, 2024)
This research explores the optimization of tourist destination selection in Karawang using the FuzzyTOPSIS method, which combines fuzzy logic and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). With data from 42 tourist destinations, five main criteria (Ticket Cost, Facilities, Security, Cleanliness, and Access Road) were analyzed. The implementation of FuzzyTOPSIS involves label encoding, normalization, membership function application, data fuzzification, determination of weight matrices, positive and negative ideal solution calculation, alternative distance calculation, and ranking. System evaluation was conducted through black-box testing by five system experts, resulting in an average Mean Opinion Score (MOS) of 76.8%. The findings indicate that the system provides satisfactory tourist destination recommendations. Suggestions for further development include direct user involvement in the evaluation and collection of qualitative feedback to gain a deeper understanding of the user experience. This research contributes to the development of a more optimal tourist destination selection system